Innovative housing policy tools: impact indicators in the NRRP Urban Regeneration Programmes - Adolfo Francesco Lucio Baratta; Laura Calcagnini; Fabrizio Finucci; Antonio Magarò (Vitruvio: International Journal of Architectural Technology and Sustainability)
The topic of indicators as measurers of the effectiveness of urban and housing transformations strongly re-emerge because of the performance approach the funding of the National Recovery and Resilience Plan (NRRP) is based on. Within the NRRP specific programmes, the issue of performance measurability of interventions was managed with the application of different indicators and application methods. The research group had the opportunity to work on the construction of a system of indicators for a national urban regeneration programme, financed within the NRRP.